The effect of different jubah dress’ materials on image quality using computed radiography (CR) on knee X-ray - Amran, Umi Nadrah; Mohd Rais, Nur Nadiah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2018)
Introduction: In medical imaging practice, the act of removing any clothes from the region of interest is justified as to prevent the presence of artefacts on radiographs. However, by doing so, the ‘aurah’ of the patients, especially for the Muslims, are not observed and can be considered as violating their privacy if they are not wellinformed beforehand. Previous studies have proved that radiographs with the presence of some fabric materials on the region of interest are radiographically acceptable. Therefore, the aims of this study are to tackle the issue of exposing one’s ‘aurah’ for a knee x-ray examination to take place and also to add insufficiency from the previous studies. Methods: The effect of three different jubah dress’ materials; heavy dull satin, high quality lycra and moss crepe on radiographic image quality for both anteroposterior (AP) and lateral knee x-ray examinations are evaluated. The effect on radiographic image quality by the manipulation of tube potentials on each jubah dress’ materials are also evaluated. A bovine’s knee is used to simulate human’s knee as opposed to previous studies which only utilized KYOTOKAGAKU phantom. Four experienced observers blindly graded image quality using Visual Grading Analysis (VGA). Results: This study shows that all three of the jubah dress’ materials produce no artefacts on images and at the same time, present no significant effect on radiographic image quality. The manipulation of tube potentials on each jubah dress’ materials also equally gives the same result. However, some increment to tube potentials is recommended to improve image quality. Conclusions: It can be concluded that a knee x-ray examination can be done without the need to remove either heavy dull satin, high quality lycra or moss crepe.